FASTING TECHNIQUES – CHANGING THE WAY, YOU LOOK AT THERAPY - DATTA, TANUDEEP; AZAMTHULLA, MOHAMMAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
At present, various complications such as diabetes, cardiovascular diseases, cancer, and neurological disorders have become treatable, almost completely, but the drugs used for the treatment may cause some severe side effects such as hypoglycemia, kidney complications, diarrhea, anemia, rashes, dyskinesia, insomnia, hypotension, confusion, hallucinations, compulsive behavior, and neurological complications. Some treatments cause defects in whole organ systems including damage to the immune system, lungs, heart, nerve endings, and reproductive organs. Many treatment approaches are using non-pharmacological techniques for treating diseases, without synthetic drugs. One such technique is fasting, a process where starvation conditions are imitated voluntarily. Intermittent fasting is done in ratios of fasting and food intake, where a person deprives himself of food for 16 h and food intake is followed for the rest of 8 h. Alternate day fasting includes alternate days of food intake and fasting. Time-restricted feeding is done by allowing food consumption only during the metabolically active phase of the day. Fasting mimicking diet is done by reducing food intake to very small levels which mimics the conditions of fasting. Reported beneficial effects of fasting have been found in diseases such as cancer, blood pressure disorders, autoimmune diseases, fibrosis, inflammation, insulin sensitivity, and oxidative stress.